The first Neanderthal specimen from Serbia: Maxillary first molar from the Late Pleistocene of Pešturina Cave. Issue 131 (June 2019) - Radović, Predrag; Lindal, Joshua; Mihailović, Dušan; Roksandic, Mirjana
Abstract: Neanderthals were the only human group in Europe throughout the Late Pleistocene until the arrival of modern humans, and while their presence has been confirmed in the surrounding regions, no Neanderthal fossils are known to date from the Central Balkans. Systematic excavations of Pešturina Cave (Serbia) resulted in the discovery of a permanent right M 1 (Pes-3). The specimen was recovered from stratigraphic Layer 4b with an estimated age of 102.4 ± 3.2 ka, associated with Mousterian artifacts. The exceptional state of preservation and minimal wear of the molar enabled a detailed description and comparative analysis of the inner and outer dental structure, including non-metric dental traits and morphometric features of the crown, roots, and dental tissues. The results of this study strongly support the identification of Pes-3 as Neanderthal. Non-metric traits of the occlusal surface of the crown, enamel-dentine junction, and roots are consistent with Neanderthal morphology. The crown shows morphometric features typical for Neanderthal M 1, such as a buccolingually skewed crown shape, internally compressed cusps, and a relatively large hypocone. The specimen also shows Neanderthal-like dental tissue proportions, characterized by relatively thin enamel and large coronal dentine and coronal pulp volumes. The discovery of the Pes-3 molar therefore confirms the presence of Neanderthals in the territory of Serbia and the Central Balkans at the end of Marine Isotope Stage (MIS) 5c.